The effect of member savings, total assets, and member loans on SHU in the Swastisari Kupang Cooperative - Anggut, Paskalis Yuvensi; Hernawati, Retno; Aboladaka , Jacob (Privietlab, 2026)
This study is motivated by fluctuations in the Operating Surplus net profit at Credit Union Loan (Kopdit Swastisari Kupang), which indicates problems in the financial performance of cooperatives. This study aims to analyze the influence of member savings, total assets, and member loans on SHU in KSP Kopdit Swastisari Kupang. The research approach is quantitative, utilizing secondary data in the form of cooperative financial statements for the 2016–2024 period. Data analysis was performed using multiple linear regression preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that the savings of some members and total assets had no significant effect on SHU, while member loans had a negative and insignificant effect on SHU. Simultaneously, the results of the F-test show that member savings, total assets, and member loans together affect SHU, but the effect is not statistically significant. These findings suggest that the increase in SHU is not entirely determined by the amount of savings, assets, and loans but is also influenced by the effectiveness of the cooperative's financial management. Therefore, KSP Kopdit Swastisari Kupang must optimize deposit management, utilize assets productively, and strengthen credit risk management to improve operational efficiency and encourage sustainable SHU growth.